Biosimilarity under stress: A forced degradation study of Remicade® and Remsima™. Issue 7 (3rd October 2017) - Pisupati, Karthik; Benet, Alexander; Tian, Yuwei; Okbazghi, Solomon; Kang, Jukyung; Ford, Michael; Saveliev, Sergei; Sen, K. Ilker; Carlson, Eric; Tolbert, Thomas J.; Ruotolo, Brandon T.; Schwendeman, Steven P.; et al.
ABSTRACT: Remsima™ (infliximab) is the first biosimilar monoclonal antibody (mAb) approved by the European Medical Agency and the US Food and Drug Administration. Remsima™ is highly similar to its reference product, Remicade®, with identical formulation components. The 2 products, however, are not identical; Remsima™ has higher levels of soluble aggregates, C-terminal lysine truncation, and fucosylated glycans. To understand if these attribute differences could be amplified during forced degradation, solutions and lyophilized powders of the 2 products were subjected to stress at elevated temperature (40–60°C) and humidity (dry-97% relative humidity). Stress-induced aggregation and degradation profiles were similar for the 2 products and resulted in loss of infliximab binding to tumor necrosis factor and FcγRIIIa. Appearances of protein aggregates and hydrolysis products were time- and humidity-dependent, with similar degradation rates observed for the reference and biosimilar products. Protein powder incubations at 40°C/97% relative humidity resulted in partial mAb unfolding and increased asparagine deamidation. Minor differences in heat capacity, fluorescence, levels of subvisible particulates, deamidation and protein fragments were observed in the 2 stressed products, but these differences were not statistically significant. The protein solution instability at 60°C, although quite significant, was also similar for both products. Despite the small initial analytical differences, Remicade® and Remsima™ displayed similar degradation mechanisms and kinetics. Thus, our results show that the 2 products are highly similar and infliximab's primary sequence largely defines their protein instabilities compared with the limited influence of small initial purity and glycosylation differences in the 2 products.